THE EFFECTIVENESS OF THE IMPLEMENTATION OF TECHNOLOGY SUBSTITUTING INPATIENT TREATMENT DURING THE MEDICAL CARE PROVISION TO WOMEN WITH BENIGN GYNECOLOGICAL NEOPLASMS - A. A. Lobganidze; B. L. Tsivyan (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2017)
Relevance. Over the last decades, such technology substituting inpatient treatment as outpatient treatment has been actively discussed and used in practice. Despite this fact, many problems of outpatient treatment have not been solved in full, no effective leverages contributing to creating economic incentives for increasing the volume and range of medical services in day hospitals have been found in the mandatory medical insurance system.Objective. Based on an in-depth analysis of medical care provision to women with benign gynaecological neoplasms, to offer measures for improvement of medical care in outpatient facilities, particularly by using technologies substituting inpatient treatment, and to evaluate their effectiveness.Materials and methods. A comprehensive retrospective evaluation of outpatient and inpatient medical care was conducted in St. Petersburg over the period from 2008 to 2015. The information contained in the database of billed and paid invoices of the obligatory medical insurance system of St. Petersburg was studied. For the total period of eight years, the data on medical care provision to 81 622 women suffering from benign tumors of the female reproductive organs, particularly in day hospitals, were obtained. In the period 2015–2016, medical care provision to patients with benign neoplasms of the gynecological sphere was thoroughly analyzed. In 18 women’s health departments and 19 in-patient facilities in all districts of the city, all cases of treatment of patients in the basic women’s health departments and in-patient facilities were analyzed by experts. By Taking into account the obtained results, an organizational experiment on introducing substituting technologies followed by evaluating the effectiveness of their use was developed and implemented on the basis of the medical institutions in one of the districts of St. Petersburg.Results. The activeness of outpatient facilities for treatment of women with benign neoplasms of the gynecological organs within the system of mandatory medical insurance has been constantly decreasing: in 2008, the services of outpatient facilities were provided by 26 health institutions, in 2015 - only by 11.The costs for treatment of patients with such diseases were analyzed, and differences were found in the approaches practiced in different districts of St. Petersburg. Low hospitalization levels predetermine active work for early detection, treatment and rehabilitation of patients at the outpatient stage, however, the study showed that in the districts with low incidence of women’s hospitalization, high detection rates are not always the case for these diseases at the outpatient stage. Such cases can result from inadequate tactics for treatment of patients at the outpatient stage, when patients not requiring 24-hour medical supervision get into an inpatient facility. Given the problems identified during the retrospective analysis, in the framework of the research conducted, approaches to arranging the treatment of patients based upon interaction between the inpatient and outpatient lings were suggested. On the basis of the Gynecological Department of a district inpatient facility, 4 outpatient beds were provided. The data analysis of the institutional experiment showed the absence of any significant dynamics in the general hospitalization levels (113.6 per 100 thousand of the adult population in 2012 112.0 per 100 thousand of the adult population in 2016, t < 2). At the same time, the incidence of urgent and and day-to-day hospitalization decreased significantly: urgent hospitalization was 11.6 per 100 thousand of the adult population in 2012 and 9.0 per 100 thousand of the adult population in 2016 (t = 3.9; p < 0.05); the figure of day-to-day hospitalization was 7.0 per 100 thousand of the adult population in 2012 and 5.5 per 100 thousand of the adult population in 2016, t = 2.7; p<0.05).Conclusions. Improvement of outpatient medical care provision to patients with benign tumors of the female genital system is possible through an active use of technologies substituting inpatient modalities, such as outpatient treatment. The experiment showed that effective monitoring of patients is possible only with close cooperation between medical institutions at all levels and building trust relationship between the doctor and the patient.